Absolute and relative lymphocyte counts in dengue infection - Bambang Ardianto Bambang Ardianto (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2002)
Background: Dengue infection is one of Indonesia's health problems. Lymphocytes are thought to be involved in dengue pathogenesis.Objectives: To determine whether there were any differences on absolute and relative lymphocyte counts between dengue and non-dengue febrile patients and among dengue fever (DF), dengue hemorrhagic fever without shock (DHFï€´, dengue shock syndrome (DSS), and non-dengue (ND) patients.Methods: A cross-sectional study was conducted on dengue and non-dengue patients hospitalized at